Utilization of Waste in Cultivating Creativity of P5-Based Class IV Students In Elementary School - Viona Nova Romandhoni; Achmad Fathoni (Lectura: Jurnal Pendidikan)
This research was motivated by the low creativity of students in utilizing waste. Even though at school students have been provided with trash bins according to their type. This study aims to analyze the stages of P5 through the use of waste in fostering student creativity as well as the supporters and obstacles in fostering student creativity at SD Muhammadiyah PK Kottabarat. The research method used used a qualitative approach with a case study type of research. Data collection techniques through observation, interviews, and documentation. The data analysis technique uses an interactive model. Data validity uses triangulation of techniques and sources. The results of this study indicate that (1) There are four stages in the implementation of the project including: a) Introduction, the activity is to find information on the utilization of used goods around and clean Friday at my school; b) Contextualization, the activities are outing projects and formative assessments; c) Action, the activities are the "Towards SD PK Zero Waste" movement campaign and making works from used goods; and d) Reflection, the activity is to carry out product exhibitions (2) Supporting and inhibiting factors in fostering student creativity through the utilization of waste, supporting factors can come from the school. while the inhibiting factors are requiring a long time and lack of consistency in completing an activity.